2021
DOI: 10.1007/978-3-030-72465-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Privacy in Payment in the Age of Central Bank Digital Currency

Abstract: In academia and at central banks, central bank digital currency (CBDC) is increasingly being researched due to the continuous decline in cash payments and the emergence of private stablecoins such as Libra. While CBDC offers various advantages for central banks, sensitive transaction and holdings data of individuals and users need to be protected. This paper analyses how privacy in payment is being discussed in CBDC related literature and pilot projects of central banks. Central banks rarely identify privacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The third group illustrates CBDCs' security and privacy. Fu et al (2019), Tronnier (2021 and Borgonovo et al (2021) demonstrated the significance of anonymity for increasing the overall attraction of CBDCs' social medium payment. Lee et al (2021c) conducted a survey on security and privacy in blockchain-based CBDCs to address the remaining security and privacy research gaps, and a techno-legal taxonomy of methodologies was further proposed to balance CBDCs privacy and transparency without impeding accountability (Pocher and Veneris, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The third group illustrates CBDCs' security and privacy. Fu et al (2019), Tronnier (2021 and Borgonovo et al (2021) demonstrated the significance of anonymity for increasing the overall attraction of CBDCs' social medium payment. Lee et al (2021c) conducted a survey on security and privacy in blockchain-based CBDCs to address the remaining security and privacy research gaps, and a techno-legal taxonomy of methodologies was further proposed to balance CBDCs privacy and transparency without impeding accountability (Pocher and Veneris, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This ameliorates the dilemmas facing modern monetary policies, such as inefficient policy transmissions, difficult regulation of conversion periods, the flow of money from the real economy to the virtual one, and the failed realisation of expected requirements by monetary policies. Moreover, capital flow information can be fully and quickly investigated, thereby aiding anti-corruption, anti-money laundering, anti-terrorist financing, and anti-tax evasion efforts [Tronnier, 2021;Dupuis et al, 2021]. Third, CBDCs have the potential to promote financial market stability by adjusting monetary, mitigating financial systemic risk, reducing shadow banking, among others [Larina and Akimov, 2020;Copeland, 2020;Zams et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of definition, financial technology (or Fintech) is defined as the use of technology and software to improve the processes of financial institutions and to improve the delivery of financial services to end users (Vives, 2017; Ozili, 2018). CBDC is commonly defined as money available in digital or electronic form (Tronnier, 2020). Cryptocurrency is commonly defined as a digital currency in which encryption techniques are used to regulate the generation of units of currency and to verify the transfer of funds without needing a financial intermediary or central bank (Lexico, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the CBN in launching the eNaira envisages that it will improve cross-border trade, increase financial inclusion, make diaspora remittances cheaper and faster, enhance direct social and welfare payments and make tax revenue collection easier. Moreover, capital flow information can be fully and quickly investigated, thereby aiding anti-corruption, anti-money laundering, anti-terrorist financing, and anti-tax evasion (Tronnier, 2021;Dupuis, Gleason & Wang, 2021). The success of Nigeria's eNaira could pave the way for other countries to adopt CBDC.…”
Section: Introductionmentioning
confidence: 99%